Examining Temperature and Water Evaporation on Turmeric: An Innovative Product of Turmeric Stick - Intan Kusumawati; Putut Marwoto; Ani Rusilowati; Woro Sumarni; Sudarmin Sudarmin; Andi Mursidi (Universitas Negeri Semarang, 2022)
Turmeric is used by cultural communities to treat nasal congestion in infants with different methods, curcumin in turmeric is scars on the skin, and innovation in turmeric is needed. This study aims to compare the temperature and water evaporation of burnt turmeric (Sample Turmeric A), turmeric mixed with whiting (Sample Turmeric B), and natural turmeric (Sample Turmeric C); determine the appropriate sample treatment to treat nasal congestion in infants; produce innovative products to treat turmeric discoloration on the skin in the use of turmeric. This research is an experiment, a preliminary study in the form of interviews and in-depth observations of the community about the use of turmeric for health that is usually carried out by cultural communities, then analyzed across the fields of STEAM-2C so that comparison results and innovative products are found in the form of Turmeric Stick. It was found that the temperature of the Turmeric A sample was 309.3 K, the B turmeric sample was 305.2 K, and the C turmeric sample was 308.1 K. The comparison of evaporation of turmeric Samples A (95666.49): Sample B (93147.04): Sample C (94925.61) is 1: 1: 1, evaporation of water through the Hertz-Knudsen equation. The conclusion is that variant C is more appropriate for dealing with nasal congestion in infants, and the turmeric innovation product in the form of turmeric sticks is a turmeric packaging solution to overcome the problem of turmeric color that causes scars.